Municipal variations in the housing arrangements of international students - Feng Hou; Max Stick; Haozhen Zhang (Economic and Social Reports)
Understanding how international students use the housing market across different municipalities can inform policy and planning decisions regarding housing supply, urban infrastructure and services to better accommodate the needs of a diverse student population. This study uses the 2021 Census of Population to examine the extent to which international students engage in the rented and owned housing sectors and the share of students living in roommate households within these markets. The results show that the majority of international students depend on the rental market for their housing needs, ranging from 65% in Brampton to 92% in Montréal across the municipalities analyzed. International students living in rented homes were more likely to reside in roommate households than those living in owner-occupied homes. Among those living in owner-occupied homes, a large proportion were subtenants who likely paid rent but were not counted in the rental market. Across municipalities, there was substantial variability in the housing arrangements of international students, mostly reflecting the availability of rented housing stock and the sociodemographic characteristics of international students.